Multiclade Human Immunodeficiency Virus Type 1 Envelope Immunogens Elicit Broad Cellular and Humoral Immunity in Rhesus Monkeys - Seaman, Michael S. (American Society for Microbiology, 2005)
The development of a human immunodeficiency virus type 1 (HIV-1) vaccine that elicits potent cellular and humoral immune responses recognizing divergent strains of HIV-1 will be critical for combating the global AIDS epidemic. The present studies were initiated to examine the magnitude and breadth of envelope (Env)-specific T-lymphocyte and antibody responses generated by vaccines containing either a single or multiple genetically distant HIV-1 Env immunogens. Rhesus monkeys were immunized with DNA prime-recombinant adenovirus boost vaccines encoding a Gag-Pol-Nef polyprotein in combination with either a single Env or a mixture of clade-A, clade-B, and clade-C Envs. Monkeys receiving the multiclade Env immunization developed robust immune responses to all vaccine antigens and, importantly, a greater breadth of Env recognition than monkeys immunized with vaccines including a single Env immunogen. All groups of vaccinated monkeys demonstrated equivalent immune protection following challenge with the pathogenic simian-human immunodeficiency virus 89.6P. These data suggest that a multicomponent vaccine encoding Env proteins from multiple clades of HIV-1 can generate broad Env-specific T-lymphocyte and antibody responses without antigenic interference. This study demonstrates that it is possible to generate protective immune responses by vaccination with genetically diverse isolates of HIV-1.